Implementation of product sharing and search system on mobile platform (Part-I) - Fang, Shuwei (2013)
With the rapid development of mobile technology, the demand for smartphones has outpaced the rest of the mobile phone market over these years. Smartphones are changing the way we spend time, organize lives and connect with people. They are becoming more and more popular because of the wide variety of available mobile applications. Mobile apps development business is booming today, with hundreds new apps come out every day.